Late infection of a breast prosthesis with staphylococcus aureus in a healthy woman: a case report. Issue 3 (7th March 2022) - Dartaha, Rami; Brimo Alsaman, Muhamad Zakaria; Jobran, Afnan W M
Abstract: Infection following breast augmentation is a rare event with an incidence rate of 1–2.5%. Late onset infections following breast augmentation are very rare. Herein, we present a case of breast implant infection in a 29-year-old female patient who underwent a bilateral augmentation mammoplasty with a silicone gel prosthesis. After 8 uneventful post-operative years, she presented with right-sided signs of breast infection. She initially treated medically but without improvement. Then, she underwent surgical washout and debridement with removal of the bilateral breast implants. Culture demonstrated Staphylococcus aureus . The clinical history and management of this unusual case are described. Because most of the infections occurs in the first few weeks after augmentation mammoplasty, there is a paucity of data about late onset infections. The most common cultured organism in the early infection is S. aureus .